ANALISIS PEMETAAN BUDAYA ORGANISASI MENGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) PADA PT. ANGKASA PURA I BANDARA INTERNASIONAL AHMAD YANI SEMARANG - Cendana, Muhammad Dinka Syafiq; Djastuti, Indi (Diponegoro Journal of Management, 2016)
Airports is an important part of the transportation services industry which connecting between the aviation transportation provider with the consumers. PT. Angkasa Pura I  Bandara Internasional Ahmad Yani Semarang as a corporate which manage this access must always improve and adaptive in order to give the best sevices and consumers needs. The tranformation has done from 2010 to   change vision, mission and values of corporate is   an effort to make positive changes. This research aim to mapping current organizational culture and worker expectation for future as input for corporate if the current and expected organizational culture still compatible with corporate’s value so PT. Angkasa Pura I  Bandara Internasional Ahmad Yani Semarang always ready to face the changes and demands of consumers.This  research  use  the  Organizational  Culture  Assessment  Instrument  (OCAI) survey method. The survey was conducted at the level of General Manager as leader, Departement Head, Section Head, dan Staff with quantitative descriptive approach so it can be analyzed and identified current and expected organizational culture profile of PT. Angkasa Pura I  Bandara Internasional Ahmad Yani Semarang.The results obtained in this study was the difference in organizational culture that is felt nowadays by Staff with job level above. The dominant organizational culture is currently perceived by General Manager, Departement Head and Section Head is a hierarchy culture. But the dominant organizational culture is currently perceived by Staff is a clan culture. Then, a similar case founded which there is  difference in organizational culture that is felt today by General Manager with job level below. General Manager expects a hierarchy culture to be the most dominant. But,   Departement Head, Section Head and Staff expects a clan culture. This cultural profile picture can be use as input for corporate to  policy  making  to  create  organizational  culture  that compatible  with the corporate’s vision dan mission.